When and How to Combine Antiplatelet and Anticoagulant Drugs? - Espinola-Klein, Christine (Hämostaseologie, 2022)
Antiplatelet and anticoagulant drugs work at different places in the coagulation system. Antiplatelet drugs are usually indicated in patients with atherosclerosis. Anticoagulant drugs are mostly used in patients with atrial fibrillation, venous thromboembolism, or technical heart valves. In some clinical situations, combination of antiplatelet and anticoagulant therapy can be indicated. The most recent situations are a more intensive antithrombotic therapy for risk reduction in patients with atherosclerosis and temporary addition of antiplatelet drugs in patients with indication for long-term anticoagulation. Temporary combination of antiplatelet and anticoagulant drugs is usually necessary after coronary intervention in patients with atrial fibrillation. In patients with high-risk atherosclerosis, the combination of low-dose rivaroxaban and aspirin reduces major adverse cardiovascular events (myocardial infarction, stroke, cardiovascular death) and major adverse limb events. But every combination of antiplatelet and antithrombotic drugs can increase bleeding risk. Therefore, a careful assessment of thrombotic versus bleeding risk is necessary for each patient.
Keywords: antiplatelet drugs; anticoagulant drugs; bleeding risk; thrombotic risk; prognosis